MUZÍKA SABAǴÍNDA «VENA KLASSIK MEKTEBINIŃ WÁKILLERI» TEMASÍN OQÍTÍWDA INTERAKTIV METODLARDAN PAYDALANÍW - Axetova, G.J. (SCIENCE and SOCIETY, 2025)
This article talks about using interactive methods in music lessons. Materials about representatives of the Vienna classical school are considered. The rules for executing methods are noted.